2016
DOI: 10.2105/ajph.2016.303137
|View full text |Cite
|
Sign up to set email alerts
|

Medical Debt and Related Financial Consequences Among Older African American and White Adults

Abstract: African Americans incur substantial medical debt compared with Whites, and more than 40% of this is mediated by health status, income, and insurance disparities. Public health implications. In Medicare, low-income beneficiaries, especially low-income African Americans with poor health status, should be protected from the unintended financial consequences of cost-reduction strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…Little previous work has focused specifically on financial burden in older cancer survivors. Wiltshire et al reported that odds of medical debt were more than twice as high among older African‐American compared with older white survivors, similar to our findings . Davidoff et al reported that out‐of‐pocket medical costs were higher among Medicare beneficiaries with cancer than without, and that this higher burden was at least partially explained by the presence of comorbidities and lack of supplemental insurance .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Little previous work has focused specifically on financial burden in older cancer survivors. Wiltshire et al reported that odds of medical debt were more than twice as high among older African‐American compared with older white survivors, similar to our findings . Davidoff et al reported that out‐of‐pocket medical costs were higher among Medicare beneficiaries with cancer than without, and that this higher burden was at least partially explained by the presence of comorbidities and lack of supplemental insurance .…”
Section: Discussionsupporting
confidence: 87%
“…Compared with white survivors, black survivors have experienced higher out‐of‐pocket costs, a greater number of financial difficulties, and more financial burden and distress . They were also more likely to file for bankruptcy, experience cancer‐related, and other medical debt, to be contacted by a collection agency and to borrow money to pay for medical debt. Not surprisingly, consistent associations have been demonstrated between low household incomes and financial burden among cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When looking at elderly individuals, blacks also tend to be more vulnerable to financial hardship as relates it to medical bills. A national study of elderly individuals demonstrated that blacks had 2.6 times greater odds of having medical debt when compared to whites [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even with the decrease in uninsured rates among men, one in five men aged 18–64 years experience difficulty in paying medical bills ( Kaiser’s Men’s Health Survey, 2015 ). Addressing difficulties in paying medical bills has significant implications on one’s debt status ( Wiltshire, Elder, Kiefe, et al., 2016 ). Specifically, the outcomes of a 2019 study by Himmelstein et al found medical-related costs were associated with 66.5% of all bankruptcies, even after the passage of the Affordable Care Act ( Himmelstein et al, 2014 ).…”
mentioning
confidence: 99%